Deficiency in NDH-cyclic electron transport retards heat acclimation of photosynthesis in tobacco over day and night shift - Zhang, You; Fan, Yanfei; Lv, Xiaotong; Zeng, Xiyu; Zhang, Qiqi; Wang, Peng (Frontiers in Plant Science, 2023)
In order to cope with the impact of global warming and frequent extreme weather, thermal acclimation ability is particularly important for plant development and growth, but the mechanism behind is still not fully understood. To investigate the role of NADH dehydrogenase-like complex (NDH) mediated cyclic electron flow (CEF) contributing to heat acclimation, wild type (WT) tobacco (Nicotiana tabacum) and its NDH-B or NDH-C, J, K subunits deficient mutants (ΔB or ΔCJK) were grown at 25/20oC before being shifted to a moderate heat stress environment (35/30oC). The photosynthetic performance of WT and ndh mutants could all eventually acclimate to the increased temperature, but the acclimation process of ndh mutants took longer. Transcriptome profiles revealed that ΔB mutant exhibited distinct photosynthetic-response patterns and stress-response genes compared to WT. Metabolite analysis suggested over-accumulated reducing power and production of more reactive oxygen species in ΔB mutant, which were likely associated with the non-parallel recovery of CO2 assimilation and light reactions shown in ΔB mutant during heat acclimation. Notably, in the warm night periods that could happen in the field, NDH pathway may link to the re-balance of excess reducing power accumulated during daytime. Thus, understanding the diurnal cycle contribution of NDH-mediated CEF for thermal acclimation is expected to facilitate efforts toward enhanced crop fitness and survival under future climates.